Hubungan Antara Harga Diri Dengan Perilaku Cyberbullying Pada Remaja - Nur Mawaddah Adam; M Ahkam Alwi (Jurnal Psikologi TALENTA, 2023)
Cyberbullying is a phenomenon that is often found in social media users, especially teenagers. Cyberbullying is aggressive behavior that is carried out continuously against other people using social media. One aspect that can influence adolescents to do cyberbullying is self-esteem. Adolescents who cannot judge themselves well are likely to do cyberbullying to increase their self-esteem. The purpose of this study is to determine the relationship between self-esteem and cyberbullying behavior in adolescents in Parepare City. The measuring instrument used in this study is the self-esteem scale which is based on the self-esteem aspects of Coopersmith (1967) and the cyberbullying scale which is based on the behavioral aspects of cyberbullying Willard (2007). Sampling is purposive sampling according to the characteristics determined by the researcher. The data analysis technique in this study was Spearman's correlation which was processed using SPSS 25. The results showed that there was a negative relationship between the variables of self-esteem and cyberbullying, which means that the higher the self-esteem of adolescents, the lower the tendency of adolescents to become perpetrators of cyberbullying.